2016
DOI: 10.1038/srep24076
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the role of motor imagery in brain-machine interfaces

Abstract: Despite technical advances in brain machine interfaces (BMI), for as-yet unknown reasons the ability to control a BMI remains limited to a subset of users. We investigate whether individual differences in BMI control based on motor imagery (MI) are related to differences in MI ability. We assessed whether differences in kinesthetic and visual MI, in the behavioral accuracy of MI, and in electroencephalographic variables, were able to differentiate between high- versus low-aptitude BMI users. High-aptitude BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 60 publications
6
86
1
1
Order By: Relevance
“…For the present study, we, cannot follow up on this possibility, given that we did not include an MI ability or severity questionnaire. It should, however, be noted that former studies found no (Rimbert et al, 2019) or rather moderate (Vuckovic and Osuagwu, 2013;Marchesotti et al, 2016) relations between subjective MI ability measures and BCI literacy.…”
Section: Study Limitationsmentioning
confidence: 72%
“…For the present study, we, cannot follow up on this possibility, given that we did not include an MI ability or severity questionnaire. It should, however, be noted that former studies found no (Rimbert et al, 2019) or rather moderate (Vuckovic and Osuagwu, 2013;Marchesotti et al, 2016) relations between subjective MI ability measures and BCI literacy.…”
Section: Study Limitationsmentioning
confidence: 72%
“…The use of objective questionnaires has been proposed in order to determine whether a person will be able to use motor imagery effectively [42]. Miller et al found that activation in M1 during motor imagery, measured using electrocorticography (ECoG), can be increased via training with feedback and that in some cases it can exceed the original motor execution levels [28].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, we discuss the classifier performance of the computed PSD vectors of contribution, ρ r,∆ f . In each one of the tested scenarios for spectral bandwidths of interest, parameter tuning is carried out to achieve the maximum accuracy within the MI interval [3][4][5], s. As seen in In terms of the tuned CNN parameters, their values averaged across the subject set show that the training scenario achieving the best accuracy (µ∪β low ∪β med ∪β high ) demands from the PSD-based vectors more hidden units hu than in the case of CWT planes. A similar situation holds in the scenario µ∪β that also performs high accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main challenges in implementing MI practice is to recognize and identify the imagined actions since EEG signals have substantial intra and inter subject variability [5].…”
Section: Introductionmentioning
confidence: 99%